Genetic variants related to angiogenesis and apoptosis in patients with glioma - Calastri, Maria Clara Jessica; Rodrigues, Nicolas Luz Toledo Ortega; Hatori, Gabriela; Gregório, Michele Lima; Brancati, Camila Ive Ferreira Oliveira; Zanovelo, Eliane Milharcix; Ferraz, José Roberto Lopes, Filho; Neiva, Cassiano Merussi; Rodrigues, Antonio Carlos Ponde, Junior; Godoy, Moacir Fernandes de; Lancelloti, Carmen Lucia Penteado; Tognola, Waldir Antonio; Souza, Dorotéia Rossi Silva (Arquivos de Neuro-Psiquiatria, 2018)
Background Glioma, the most common primary malignant brain tumor in adults, is highly aggressive and associated with a poor prognosis. The objectives of this study were to evaluate the association of genetic polymorphisms related to angiogenesis and apoptosis with gliomas, as well as comorbidities, lifestyle, clinical profile, survival and response to treatment (temozolomide [TMZ] and radiotherapy [RT]) in patients with the disease.Methods In a total of 303 individuals, genotypes were performed by real-time PCR, and clinical data, lifestyle and comorbidities were obtained from medical records and questionnaires. The significance level was set at 5%.Results Smoking, alcohol consumption, systemic arterial hypertension, diabetes mellitus and body mass index prevailed among patients, compared to controls (p < 0.05). The heterozygous genotype rs1468727 (T/C) and the homozygous genotype rs2010963 (G/G) (p > 0.05) were observed in both groups. Lifestyle and comorbidities showed independent risk factors for the disease (p < 0.0001, p = 0.0069, p = 0.0394, respectively). Patients with low-grade gliomas had a survival rate of 80.0 ± 1.7% in three years. For the combination of TMZ+RT, survival was 78.7 ± 7.6% in 20 months, compared to TMZ only (21.9 ± 5.1%, p = 0.8711).Conclusions Genetic variants were not associated with gliomas. Specific lifestyle habits and comorbidities stood out as independent risk factors for the disease. Low-grade gliomas showed an increase in patient survival with TMZ+RT treatment.
Keywords: central nervous system; genes, erbB-1; glioblastoma